2017
DOI: 10.1037/tam0000090
|View full text |Cite
|
Sign up to set email alerts
|

The state of scientific knowledge regarding factors associated with terrorism.

Abstract: We conducted a systematic review of the contemporary scientific literature to (a) identify consensus, where it exists, regarding factors associated with membership in terrorist organizations and/or perpetration of terrorist attacks; (b) drive future research directions; and (c) inform evidence-based counterterrorism strategies. Systematic searches of 6 databases identified 205 articles that met inclusion criteria. Of these, 50 articles reported on findings of empirical research, 24 reported inferential statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
62
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 196 publications
2
62
1
1
Order By: Relevance
“…Likewise, uncontrolled descriptive studies of terrorists have yielded to comparative studies, such as ideologically motivated versus non-ideological mass murderers (Horgan, Gill, Bouhana, Silver, & Corner, 2016); individual terrorists versus autonomous cells in Europe (Meloy, Roshdi, et al, 2015); jihadist versus single-issue versus right wing terrorists (Gill, Horgan, & Deckert, 2013); terrorists versus murderers in Iraq (Dhumad, Candilis, Cleary, Dyer, & Khalifa, 2019); and violent versus non-violent extremists in the UK (Knight, Woodward, & Lancaster, 2017). These efforts have all contributed to the disaggregation of the meaning of "terrorist" and "terrorism" (Desmarais, Simons-Rudolph, Brugh, Schilling, & Hoggan, 2017) and the recognition that differences in static (e.g., age, education, history of criminality) and dynamic (e.g., roles, pre-offense behaviors) characteristics yield more operationally relevant data (Borum, 2015) and help to bridge the gap between academia and pragmatic efforts at prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, uncontrolled descriptive studies of terrorists have yielded to comparative studies, such as ideologically motivated versus non-ideological mass murderers (Horgan, Gill, Bouhana, Silver, & Corner, 2016); individual terrorists versus autonomous cells in Europe (Meloy, Roshdi, et al, 2015); jihadist versus single-issue versus right wing terrorists (Gill, Horgan, & Deckert, 2013); terrorists versus murderers in Iraq (Dhumad, Candilis, Cleary, Dyer, & Khalifa, 2019); and violent versus non-violent extremists in the UK (Knight, Woodward, & Lancaster, 2017). These efforts have all contributed to the disaggregation of the meaning of "terrorist" and "terrorism" (Desmarais, Simons-Rudolph, Brugh, Schilling, & Hoggan, 2017) and the recognition that differences in static (e.g., age, education, history of criminality) and dynamic (e.g., roles, pre-offense behaviors) characteristics yield more operationally relevant data (Borum, 2015) and help to bridge the gap between academia and pragmatic efforts at prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for violent extremism can serve as markers to inform the detection and disruption of terrorist threats. A systematic review showed that age, socioeconomic status, prior arrest, education, employment, relationship status, having a grievance, geographic locale, and type of geographic area, are factors associated with violent extremism . Other systematic reviews, rapid evidence assessments, and research syntheses report similarly .…”
Section: Introductionmentioning
confidence: 98%
“…Empiricism in terrorism studies is increasing . One systematic review of factors associated with violent extremism found 50 empirical articles . Studies typically cover areas concerning socio‐demographic characteristics, criminal history, religion and spirituality, work and education, personal experiences, attitudes and beliefs, relationships, mental health, motivation, radicalizing processes, and environmental factors .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, others have also noted the need for more empirical research in this area, for primary sources of data to be used and for the gap between academic research and counterterrorism intelligence (in terms of data sharing and the skills needed to make sense of this) to be narrowed (e.g. Borum, 2012;Desmarais, Simons-Rudolph, Brugh, Schilling, & Hoggan, 2017;Ranstorp, 2007;Schmid, 2016;Schuurman, 2018). This longstanding self-reflection by those seeking to understand terrorism demonstrates that researchers are not ignorant to the limitations associated with this field of study, and that serious attempts to address these have been made.…”
Section: Introductionmentioning
confidence: 99%